2004
DOI: 10.1590/s0104-42302004000100040
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação do stone clinic effect em pacientes com nefrolitíase

Abstract: The "stone clinic effect" significantly decreased urinary SS for calcium oxalate and the formation of new kidney stones in 80% of patients during first year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
5
Order By: Relevance
“…9,12,28,29 Também é interessante o estudo metabólico do indivíduo, visando à identificação e correção, de forma econômica e eficiente, dos desequilíbrios entre as substâncias que podem influenciar no processo litogênico. 8 A nefrolitíase tem sido associada com hipertensão arterial sistêmica.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…9,12,28,29 Também é interessante o estudo metabólico do indivíduo, visando à identificação e correção, de forma econômica e eficiente, dos desequilíbrios entre as substâncias que podem influenciar no processo litogênico. 8 A nefrolitíase tem sido associada com hipertensão arterial sistêmica.…”
Section: Discussionunclassified
“…Em estudo que acompanhou pacientes após orientações, como aumento da ingestão hídrica, foi notado um aumento significativo no volume urinário. 12 No estudo de Carvalho et al, 12 após orientações relativas ao aumento da ingestão hídrica, diminuição do consumo de sal e proteína (em torno de 1 g/kg/dia), além da ingestão de 800 mg/dia de cálcio, houve aumento significativo na excreção de citrato (368 ± 238 vs. 502 ± 221 mg/dia). Dieta normal em cálcio e com baixas quantidades de sal e proteína diminui a excreção urinária de oxalato e de cálcio, que em combinação com o aumento da ingestão de água gera diminuição da saturação urinária, causando redução na recorrência de nefrolitíase.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…15 A retrospective review of dietary counseling has shown a 55.5% decrease in urinary oxalate in patients counseled during clinic visits. 16 Likewise, recurrent stone formation was significantly decreased in hyperoxaluric patients, 17 and the supersaturation of calcium oxalate, and thus the risk of formation of new stones was found to be decreased in up to 80% of patients after dietary counseling. 18 As access to information improves, more people are turning to the Web for medical and nutritional advice.…”
Section: Commentmentioning
confidence: 99%